Pengaruh Pendekatan Realistic Mathematics Education Terhadap Peningkatan Kemampuan Koneksi Matematis Siswa SMP - Rohantizani; Nuraina (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
This research aims to determine the effect of implementing the RME approach on students' mathematical connection abilities. The type of research used is quantitative research with pre-experimental designs (Nondesigns) research. The population in this study were class IX students of SMP IT Ummul Qura Panton Labu, North Aceh with a sample of 20 students in class IX. The data collection technique used in this research is a mathematical connection ability test divided into pretest and posttest. The analysis techniques used include normality tests, homogeneity tests, hypothesis testing using the t test, and correlation tests. Data were analyzed using SPSS version 24. The results concluded that there was an influence of applying the RME approach to students' mathematical connection abilities. This is also supported by descriptive data which shows the average posttest score is higher than the average pretest score. Furthermore, the results of the correlation test analysis show a significance value of 0.001 < 0.05 which states that there is a correlation and the Pearson correlations value = 0.664 which is included in the strong category and the direction of the relationship is positive.